Prospective ergonomics - Liem, André (Innovation, entrepreneurship, management series. Human-machine interaction set, 2017)
"This book argues for a prospective turn in ergonomics to challenge the established fields of strategic design (SD) and management. Its multi-disciplinary outlook builds upon concepts derived from Management, Innovation and Design Science. Differences, similarities and relationships between strategic design and prospective ergonomics are reviewed using existing theories and frameworks from design, ergonomics, and strategic and innovation management. To complement the theory, 12 cases have been analyzed in greater depth according to 4 main dimensions of analysis. Outcomes have shown that innovating through the Prospective Ergonomics (PE) approach is about finding the right balance between, on the one hand, meeting primary objectives such as profit maximization or solving the design problem, and on the other, acknowledging that human activity is bounded by rationality. This means that humans have diverse motives."--